2006
DOI: 10.1111/j.1348-0421.2006.tb03845.x
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cells Play Disparate Roles in the Induction and the Effector Phases of Murine Experimental Allergic Conjunctivitis

Abstract: Although CD4+ Th2 cells clearly play an essential role in the development of experimental allergic diseases, the functions CD8+ T cells may have in these diseases have been investigated less extensively and remain controversial. Here, we investigated the roles of CD8+ T cells in the development of experimental allergic conjunctivitis (EC). EC was induced in CD8α‐deficient (CD8KO) mice and wild‐type (WT) mice by active immunization with short ragweed pollen (RW) followed by challenge with RW‐containing eye drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…We have previously shown that CD8+ T cells participate in the development of EC during the induction phase [13]. It could be considered that anti-4-1BB Ab treatment affects the number of CD8+ T cells which participate in the development of EC.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that CD8+ T cells participate in the development of EC during the induction phase [13]. It could be considered that anti-4-1BB Ab treatment affects the number of CD8+ T cells which participate in the development of EC.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of the common laboratory species, mice, rats, and guinea pigs, we elected to use rabbits as the working animal model, bearing in mind that (i) numerous similarities between rabbit and human OMIS exist (13,66,67); (ii) several T-cell-mediated ocular surface diseases, including herpetic conjunctivitis and recurrent corneal herpetic stromal keratitis (HSK), have been reported to be similar in rabbits and humans, making it the most relevant animal model for exploring these human eye disorders (53,55,80); (iii) compared to mice and rats, rabbit CALT more closely resembles human CALT (23,25,28,44); (iv) microanatomy and immunohistological studies indicate that rabbit conjunctival mucosa is comparable to that of humans and has a typical follicular ultrastructure with an abundance of "conjunctival lymphoid follicles," whereas no lymphoid tissue was identified in mice and rats (28,42,43,47,84); (v) from a practical standpoint, unlike mice, rats, and guinea pigs, rabbits possess a relatively large conjunctival surface, offering abundant mucosa-associated lymphoid tissue for in vitro studies; and (vi) the recent availability of many monoclonal and polyclonal antibodies specific to rabbit immune cell CD markers, cytokines, and growth factors provide useful immunological tools for an unprecedented phenotypic and functional analysis of rabbit T-cell repertoire and function.…”
Section: Cd25mentioning
confidence: 99%
“…A recent study suggests that CD8 þ T cells promote the development of experimental allergic conjunctivitis in the induction phase, indicated by reduced conjunctival eosinophilic infiltration in ragweed-immunized/challenged CD8-deficient mice compared with wild type mice [21]. Another study found that thymus-derived CD4 þ CD25 þ T cells suppress the development of experimental allergic conjunctivitis in mice sensitized/challenged with short ragweed [22 ].…”
Section: Recent Findings In Ocular Allergy Pathophysiologymentioning
confidence: 96%